Are Information Systems Graduates Prepared for a Complex Society? - Wirkus, Tyrrell (My University, 2013)
As businesses continue to grow, they will require graduates with a cross-disciplinary knowledge and skill set. The goal of this project was to examine to what extent U.S. programs of Information Systems (IS) are aligned with their university's liberal education learning goals. Another focus of this research was to develop a model aligning relevant curricula guidelines. The purpose of this study was to determine if IS programs in the U.S. are designed to meet these emerging business requirements by preparing graduates to succeed in an increasingly complex, global society.
Color poster with text, charts, and graphs.
Keywords: Information systems--Curriculum; Graduation requirements; Posters